A study of 300 and 200 mb temperature and Wind over India in relation to forecasting Onset of monsoon - GUPTA, HN; ALI, HAMID (MAUSAM, 1985)
Monthly wind and temperature data at 300 mb and 200 mb for the month of April, t for the years 1961-77 for the stations, viz., Trivandrum, Madras, Bombay, Nagpur, Ahmedabad, Jodhpur and Delhi have been studied. Latitudinal distribution of temperature shows that at 200 mb level Bombay is on the average colder for the years of late onset of monsoon (1964, 1967, 1968, 1972 and 1973) than the years of early onset (1961, 1962, 1970 and’ 1971). At 300 mb level on an average (based on 17 years data) Bombay is warmer than Nagpur by about 0.9 deg. C. However for the years of late onset of monsoon Bombay is colder than Nagpur by 0.1 deg. C and for early onset Bombay is warmer than Nagpur by 2.3 deg. C. Mean meridional wind component at 300 mb over Bombay is northerly for the years of early onset and it is southerly for the years of late onset. Onset of southwest monsoon for 1979 (MONEX year) is also discussed.